Adaptation and acceptability testing of the Expector® vibration vest in horses - Oliveira, Gabriela Novo de; Silva, Sofia Cicolo da; Zibordi, Miriam; Barros, Aline de Matos Curvelo de; Belli, Carla Bargi (Brazilian Journal of Veterinary Research and Animal Science, 2022)
The project is based on a test of a thoracic vibration vest prototype, adapted to equines by the Expector® vest’s company, on healthy animals. Ten (10) equines were used in the project, male or female, adults, healthy, belonging to FMVZUSP or private owners. Each animal went through two phases: A and B. Phase A consisted of the placement of the vest without turning on the vibrators, evaluating the animal’s acceptability, facility, adaptation to the animal’s body, and discomfort due to the vest’s use. Phase B included the placement of the vest and turning on the vibrators, evaluating the animal’s acceptability, reaction to the vibrators, and, if present, to which velocity/type of vibration, and the presence of adverse effects. Both phases were done three times on separate days. The behavioral parameters: “placement facility” and “adaptation to the animal’s body” were observed. In phase B, the response to the vibration was classified from 0 to 5. The answer was evaluated on low and high intensities for the four vibration types. The heart rate (HR) and respiratory rate (RR) were also evaluated at the beginning and end of each repetition. The animals’ HR was kept on normal, except for one animal on one day of the test. Concerning the RR, most animals presented moments of tachypnea. On the experiment’s first day, 100% of grade Great to “facility of placement” and “adaptation to the animal’s body” was obtained, but on days 2 and 3 this value dropped to 90% due to alterations in one animal’s responses. Regarding vibration’s responses, 77.3% were evaluated as no discomfort (grade 0), 17.1% little discomfort (grade 1), 3.3% medium discomfort (grade 2), 0.4% great discomfort (grade 3), 0.21% extreme discomfort (grade 4), and 1.6% non-acceptance of the vest (grade 5). Some possible changes on the prototype were also verified to be suggested to the manufacturer, such as the change of the buckle and the use of wireless control. Vest use appears promising for equine respiratory physiotherapy, considering the acceptability was good, and its efficiency on the expectoration of diseased animals must be tested.